Perencanaan Waktu dan Biaya Menggunakan Metode Crashing Dengan Sistem Kerja Shift - Dewi Bussaina Ghassani; Ulul Albab (JERA : Journal of Engineering Research and Application, 2023)
When constructing a building project, delays in project work often occur when it is implemented. So an alternative is needed that can help complete construction projects faster, one of which is by using the labor shift method. This study analyzes the accelerated period using labor shifts at the Sukorejo II Health Center Development Project. From the data obtained after analysis, the project can be accelerated for 19 working days so that the project duration, which was originally 90 working days, became 71 working days (down 21.11%). The project's direct costs increased from Rp 2,046,947,259.07 in 90 days to Rp 2,054,582,259.07 in 71 days (up 0.4%). Indirect costs decreased from Rp 361,225,986.89 to Rp 335,806,380.41 (down 7.04%). So that the total cost of the project, which was originally IDR 2,046,947,259.07, became IDR 2,054,582,259.07 from the normal project (down 0.37%). Keywords: Construction Management, Project Acceleration, Crashing Method.